2017
DOI: 10.1016/j.jneuroling.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Second language performances in elderly bilinguals and individuals with dementia: The role of L2 immersion

Abstract: With the population aging and an increase in the number of senior immigrant citizens in modern societies, public health systems will be increasingly burdened with the need to deal with the care and treatment of bi-or multilingual individuals with cognitive decline and dementia. This raises complex questions such as which language is better preserved in these elderly individuals, particularly for those facing dementias. The main aim of the present investigation was to study in two groups of immigrant population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In addition to the benefits of language transfer identified in the attainment and maintenance of English, exposure to English emerged as a predictor of English proficiency across our overall sample, consistent with previous findings in younger adults 2 (e.g., Marian et al, 2007;Linck et al, 2009) and older adults (Barresi et al, 1998;Nanchen et al, 2017). It is possible that, in learners who cannot engage efficient cognitive control skills to ameliorate interference from other languages, establishment of languagespecific resonance through continued immersion is especially critical in the language acquisition process.…”
Section: Continued Exposure To Englishsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to the benefits of language transfer identified in the attainment and maintenance of English, exposure to English emerged as a predictor of English proficiency across our overall sample, consistent with previous findings in younger adults 2 (e.g., Marian et al, 2007;Linck et al, 2009) and older adults (Barresi et al, 1998;Nanchen et al, 2017). It is possible that, in learners who cannot engage efficient cognitive control skills to ameliorate interference from other languages, establishment of languagespecific resonance through continued immersion is especially critical in the language acquisition process.…”
Section: Continued Exposure To Englishsupporting
confidence: 89%
“…For example, Barresi et al (1998) found in a longitudinal study that older individuals who reported living in a household with other adults showed better naming performance while those who reported high-passive language exposure through television showed lower performance. In younger bilingual adults and language learners, language exposure has similarly emerged as an important predictor of abilities (e.g., Marian et al, 2007;Linck et al, 2009) and may play an important role in the maintenance of L2 in older adults (e.g., Nanchen et al, 2017). It has been suggested that continued use of a language provides continued activation and strengthens its representations, creating language-specific resonance that boosts the network underlying the novel language and reduces interference from other languages (MacWhinney, 2012).…”
mentioning
confidence: 99%
“…Language learning was also found to be related to improvement of self‐rated health and memory. Previous studies have found that language learning is related to cognitive function (Antoniou, & Wright, ), and a second language preservation ability was related to cognitive function (Nanchen et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…In fact, Abutalebi et al (2015) found that differences between L1 and L2 suggesting an age of L2 acquisition effect are not present in elderly individuals. Nanchen et al (2017) examining preservation of L1 and L2 in an immigrant population of late bilingual speakers with dementia, found that languages were equally preserved. They concluded that for elderly individuals, exposure and immersion are the main determinants of language preservation.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence is mixed. Some studies report parallel deterioration (Salvatierra et al, 2007;Costa et al, 2012;Manchon et al, 2015;Nanchen et al, 2017), while others report differential deterioration of the two languages (Mendez et al, 1999;Gollan et al, 2010). In the study by Gollan et al (2010), bilingual persons with AD exhibited greater decline in the dominant than the nondominant language.…”
Section: Introductionmentioning
confidence: 88%